ANALISIS DAN IMPLEMENTASI SISTEM INFORMASI PENJUALAN PADA PD. CITRA KOMPUTER PONTIANAK - Rian Oktavianus (STMIK PONTIANAK, 2011)
Abstracts: Research on PD Citra Computer of Pontianak include the company's working procedures from receipt of goods orders, sales returns, revenue service, and making reports. The problems are found process of slow sales transaction handling, storage and recording of sales data in the sales book,its makes finding data and presenting the information to be ineffective and inefficient. The research method used descriptive method, that is conducted in a systematic, factual, and actual. The design and developed a protoype of sales information system using Microsoft Visual Fox Pro 9.0 programming language, also the database is already integrated in Visual Fox Pro 9.0. The proposal of system generate expected to answer a variety of problems that are found, mainly for the provision of various reports with more specific information, such as sales per customer report, sales report per period, the report returns per subscriber, the report returns per period, per period of service reports, and other reports useful for leadership in conducting the analysis and decision making.Keywords : Sales Information System, Protoype, System Development Methodology, Microsoft Visual Fox Pro 9.0 .